The The Role of Giving Incentives and Workload for Employees of Bank Perkreditan Rakyat Bekasi Branch - Bintang Narpati; Kardinah Indrianna Meutia; , Endah Prawesti Ningrum (Future Science, 2022)
The purpose of this research is to measure the impact of the effect of providing incentives on the workload of employees at BPR Lestari Bekasi Branch. Quantitative descriptive analysis in this study involved 35 (thirty five) employees and used non-probability sampling. Data collected by making a questionnaire and distributed to employees of the company. From this research, it can be concluded that there is a positive and significant impact of providing incentives and workload on the variable of employee productivity at PT. BPR Lestari Bekasi Branch. The statistical test results obtained are incentives and workloads have a positive effect with a coefficient of determination of 78.70% on work productivity and partially each variable has a positive effect and significance on the dependent variable. An increase in the value of incentives and workload can increase the work productivity variable positively and vice versa if there is a decrease in the independent variable it can have an impact on a decrease in the dependent variable. Incentive variables affect the work productivity of employees of PT. BPR Lestari is indicated by the T-count > T-table value, namely (3.566 > 2.035) sig. 0.001 < 0.05 in this case the role of incentives has a positive and significant effect on employee productivity. The workload variable has an impact on the work productivity of PT. BPR Lestari. T-test results > T-table (7.391 > 2.035), sig. 0.000 < 0.05. Simultaneously the two independent variables Incentive and Workload have a positive and significant impact on the dependent variable, namely Work Productivity. The result of the Coefficient of Determination or R Square is 0.787, which means that this incentive has contributed 78.70% to the Work Productivity of PT. BPR Lestari Bekasi Branch.